An injectable and fast-degradable poly(ethylene glycol) hydrogel fabricated via bioorthogonal strain-promoted azide–alkyne cycloaddition click chemistry. Issue 30 (14th August 2015) - Jiang, Huafang; Qin, Siyong; Dong, Hui; Lei, Qi; Su, Xin; Zhuo, Renxi; Zhong, Zhenlin
<x xml:space="preserve">Abstract</x> A hydrogel was formed by subcutaneously injecting a mixture of the azide-modified poly(ethylene glycol) (PEG) and cyclooctyne-modified PEG into Kunming mice. The hydrogel showed good biocompatibility and biodegradability.